Web-Based Exercise Program Increases Cervical Strength in Adolescent Athletes. Issue 4 (April 2021) - Wilson, Julie C.; Levek, Claire; Daoud, Ariel K.; Brewer, Matthew; Brooks, Katelyn; Sochanska, Ada; Randall, Melissa; Provance, Aaron J.
Abstract : Abstract: Wilson, JC, Levek, C, Daoud, AK, Brewer, M, Brooks, K, Sochanska, A, Randall, M, and Provance, AJ. Web-based exercise program increases cervical strength in adolescent athletes. J Strength Cond Res 35(4): 1149–1155, 2021—This cohort study aimed to evaluate the efficacy of a web-based 6-week cervical strengthening program on cervical strength in adolescent athletes. It was hypothesized that subjects completing the program would demonstrate significant increase in cervical muscle strength compared with baseline strength. Eighty-three high school soccer athlete subjects were recruited from 2 local nationally competitive soccer clubs. Teams were assigned to either control or intervention groups to minimize information crossover. Fifty subjects were recruited to the intervention group (29 male, 21 female; average age 15.1 years). Thirty-three subjects were recruited to the control group (21 male, 12 female; average age 15.1 years). Intervention group subjects completed a web-based progressive cervical strengthening program over 6 weeks. Cervical strength in flexion, extension, right and left lateral flexion (LLF) was measured in Newton (N) of force at 3 time points during the competitive season for both control and intervention groups. Intervention group subjects significantly increased cervical strength [mean difference (95% confidence interval)] in LLF [24.1 (15.9–32.4)], extension [27.9 (18.4–37.5)], right lateral flexion [18.8 (11.6–26.1)], and flexion [mean ratio: 1.2 (1.1–1.2)] at follow-up testing; whereas control subjects did not see significant changes in strength. A web-based progressive cervical strengthening program improves cervical muscular strength in a population of adolescent athletes over a period of 6 weeks. Such a program could be used by researchers in future studies evaluating the influence on concussion risk and by practitioners as a means of reducing sport-related head and neck injuries. Abstract : Supplemental Digital Content is Available in the Text.